Influence of the antioxidant complex on the physical efficiency of highly qualified athletes specializing in rowing - Zukow, W.; Gozhenko, A.; Kozyrev, A. (Quality in Sport, 2019)
The publication discusses the possibility of using antioxidants to mitigate the effects of oxidative stress and increase physical performance in highly qualified athletes who specialize in rowing.